Evaluation method for flange-climb derailment focusing on contact position and transverse creepage between wheel and rail in railway vehicle - Shoya KUNIYUKI; Kimihiko NAKANO (Nihon Kikai Gakkai ronbunshu)
At present, running safety in railway vehicles against flange-climb derailment is evaluated based on derailment quotient. This approach is preferred because measuring contact forces between wheel and rail is relatively easier than measuring the contact condition, and the dynamic condition of the contact forces can theoretically determine whether the wheel climbs the rail or not. However, in recent years, methods for grasping the contact condition have been studied, which is expected to lead to future evaluations of running safety that consider the contact condition. On the premise of this background, this study proposes a new evaluation method for the running safety against flange-climb derailment in railway vehicles, focusing on the contact conditions between wheel and rail. The method utilizes two key variables: the lateral contact position and the normalized transverse creepage, defined as the ratio of transverse creepage to wheelset angle of attack. Through vehicle dynamics simulations under various running conditions, the relationship between these variables and the running safety was investigated. Results show that the transit domains for loci of these variables differ significantly between derailment and non-derailment cases. The study also reveals that wheel lateral acceleration plays a crucial role in determining derailment occurrence. This research provides fundamental insights for developing advanced safety assessment techniques in railway operations, considering detailed wheel-rail contact dynamics.